Marsha L. Wagner, The Lotus Boat, The Origins of Chinese Tz'u Poetry in T'ang Popular Culture, New York, Columbia University Press, 1984. pp xviii + 199 pp. - Maeth Ch., Russell (El Colegio de México, 1985)
-